The Economics of Innovation in Modern Russia: Practice, Problems and Prospects - Popov, Rinad A.; Sekisov, Aleksandr N.; Shipilova, Natalia A. (International Journal of Economics and Financial Issues, 2016)
In formed over the past quarter century in Russia the competitive market system has come to the fore the profitability of innovation, especially in production systems, industry and construction. Slightly less profitability factor manifests itself in the evaluation of innovations in social systems, yielding the position of the virtual indicator of socially useful significance of such innovations: the expansion and improvement of educational, children’s and medical institutions, objects of culture and sports, non-profit facilities, “relaxation” and recreation. In the latter case, the economic effect of innovation is manifested in an indirect form, and after a considerable lapse of time: in the employability and technical culture of employees, in expanding the number and improving the quality of the labor pool in the intellectualization of law and order and labour discipline (law-abiding, tolerance) etc. Keywords: innovation, economic efficiency, new appliances, security, industrial equipment and machinery, wear and tear, cluster JEL Classification: O14, Q26, Q57, Q58